(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The theory of linguistic relativity, specifically the Sapir-Whorf hypothesis, has also been examined in the context of bilingualism. While the strong version of linguistic relativity suggests that language shapes thought, the evidence remains inconclusive. However, it is clear that bilingual individuals navigate and negotiate different linguistic systems, potentially influencing their cognitive processes and worldview.